1986
DOI: 10.1109/edl.1986.26298
|View full text |Cite
|
Sign up to set email alerts
|

Inverted GaAs/AlGaAs modulation-doped field-effect transistors with extremely high transconductances

Abstract: Inverted GaAdAsGaAs MODFET's with transconductances as high as 1810 mS/mm at 77 K and 1180 mS/mm at 300 K are fabricated using a self-aligned process. The devices have the gateheterojunction interface spacing of only 100 A , and the observed values of the transconductance are limited primarily by the source series resistance and b i the gate current. The MODFET characteristics are interpreted using the charge control velocity saturation model which takes into account the gate current. The obtained results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…While most studies have been concentrated in the normal-structure HEMTs, the inverted structure HEMTs (I-HEMT), in which the small bandgap channel is on top of the large bandgap supplying layer, have also been proposed and investigated theoretically and experimentally by Lee and Shur [4], Morkoc et aL[S] and Cirillo et a1. [6]. There are several advantages of the I-HEMT structure.…”
Section: Recentlymentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies have been concentrated in the normal-structure HEMTs, the inverted structure HEMTs (I-HEMT), in which the small bandgap channel is on top of the large bandgap supplying layer, have also been proposed and investigated theoretically and experimentally by Lee and Shur [4], Morkoc et aL[S] and Cirillo et a1. [6]. There are several advantages of the I-HEMT structure.…”
Section: Recentlymentioning
confidence: 99%
“…It has been shown that the transconductance of the I-HEMT is nearly independent of the doping level in the high bandgap material, while in the normal HEMT the transconductance decreases with reduced doping [7]. Enhanced electron mobility[S] and extremely high transconductance [6] were also observed, which was attributed to the smaller distance between the 2D electrons and the gate in the I-HEMT compared with that of the normal HEMT. For power applications, high breakdown characteristics are also needed.…”
Section: Recentlymentioning
confidence: 99%